2007
DOI: 10.1038/sj.gene.6364431
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in a Japanese patient with CD19 deficiency

Abstract: Common variable immunodeficiency (CVID) is a heterogeneous disorder characterized by recurrent bacterial infections, hypogammaglobulinemia and low to normal numbers of circulating B cells. Mutations in the ICOS, TACI and CD19 genes have recently been identified in o10% of CVID patients. We, herein, describe two novel CD19 gene disruptions in an 8-year-old Japanese boy, who had been clinically diagnosed as having CVID at the age of 5 years. Flow-cytometric analysis demonstrated absence of CD19 and reduced CD21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 19 publications
6
80
0
2
Order By: Relevance
“…Our observations of reduced CD19 and CD21 membrane expression in 30 carriers of a CD19 gene mutation confirm and strengthen earlier observations. 5,6 The 2.4-fold reduction of CD19 in carriers clearly showed that two functional alleles are required for normal CD19 membrane expression levels on B cells, and that the loss of one allele cannot be compensated for by the remaining functional allele. Furthermore, the 1.3-fold decrease in CD21 membrane expression in carriers shows the tight relation between CD19 and CD21 on mature B cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our observations of reduced CD19 and CD21 membrane expression in 30 carriers of a CD19 gene mutation confirm and strengthen earlier observations. 5,6 The 2.4-fold reduction of CD19 in carriers clearly showed that two functional alleles are required for normal CD19 membrane expression levels on B cells, and that the loss of one allele cannot be compensated for by the remaining functional allele. Furthermore, the 1.3-fold decrease in CD21 membrane expression in carriers shows the tight relation between CD19 and CD21 on mature B cells.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 In fact, several CD19-deficient patients have high levels of autoantibodies either with or without an autoimmune disease. 5,6,25 Because only five CD19-deficient patients have been described so far, it cannot be concluded whether loss of CD19 is associated with increased autoimmunity. BCR-mediated signaling and Toll-like receptor-mediated signaling in precursor B cells are important for the removal of autoreactive B-cell receptors, as patients with genetic defects in BTK or MyD88 have been shown to have increased number of B cells carrying autoreactive BCRs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations